Long-term phycoremediation of hydroponic drainwater in a pilot-scale turbidostat - Borhan, Emren; Korhonen, Ville; Sirin, Sema; Allahverdiyeva, Yagut (Elsevier, 2026)
Drainwater from hydroponic greenhouse production presents environmental and regulatory challenges for discharge due to high concentrations of nitrogen and phosphorus. Microalgae-based treatment (phycoremediation) has been proposed as an integrated solution to recover nutrients and mitigate effluent impact, but its long-term performance under seasonally variable, low-irradiance greenhouse conditions remains to be evaluated.
Here we report the performance of continuous phycoremediation using green microalgae Scenedesmus sp. NIVA-CHL 99 cultivated in 1000 L closed tubular vertical photobioreactor (PBR) treating commercial cucumber greenhouse effluent (N–NO3: 233–422 mg L−1; P–PO4: 21–49.5 mg L−1). Sixteen operations were conducted over one year (April 2024 – May 2025) under batch, chemostat, and turbidostat modes with varied hydraulic retention times (HRT: 5–20 days [d]) and solids retention times (SRT: 2.5–5 d) in Nordic greenhouse environment.
Turbidostat operation at an intermediate OD setpoint (OD890 = 1.2) resulted in most effective overall performance, achieving robust nitrate removal (26.1 mg N–NO3 L−1 d−1) and biomass productivity (0.55 g DW L−1 d−1), while consistently meeting European Union (EU) discharge limits (TN < 6 mg L−1; TP < 0.5 mg L−1). Low-OD (OD890 = 0.9) turbidostat reached 41.1 mg N–NO3 L−1 d−1 but compromised discharge quality. Chemostat modes yielded high biomass productivity (0.68 g DW L−1 d−1) with less treatment flexibility. Light, temperature, and HRT/SRT effects on daily nutrient removal and biomass productivity were evaluated.
This study demonstrates the operational balance of greenhouse-integrative phycoremediation between drainwater treatment capacity, discharge compliance, and biomass productivity. Continuous turbidostat phycoremediation combines nutrient recovery with stable algal biomass production, reducing reliance on synthetic fertilizers and lowering operational costs. The approach advances year-round, scalable microalgal cultivation in the Nordics while transforming drainwater into resource stream within circular bioeconomy framework.